Leucemia linfática crónica: efecto de los nuevos agentes terapéuticos sobre el clon leucémico y las células del microambiente tumoral - Elías, Esteban Enrique (2020)
Chronic lymphocytic leukemia (CLL) is characterized by the accumulation of clonal\nmature B cells in peripheral blood and lymphoid tissues. Leukemic cells survive and\nproliferate in lymphoid tissues receiving signals through the B cell receptor and signals\nprovided by activated T cells, myeloid cells and stroma. The aim of our study was to find\na rational combination of therapeutic agents in vitro in order to improve the treatment of\nCLL patients. We found that leukemic cells are highly sensitive to venetoclax (BCL-2\ninhibitor) compared to T cells, NK cells and monocytes of CLL patients. Autologous T\ncell activation favors leukemic cell resistance to venetoclax and selects CLL cells with an\naggressive phenotype. Entospletinib (SYK inhibitor) impairs venetoclax resistance.\nMoreover, we found that venetoclax does not affect antibody dependent cellular\ncytotoxicity by NK cells, which is inhibited by entospletinib. Finally, we observed that\nvenetoclax enhances rituximab-coated CLL cells phagocytosis, even in the presence of\nentospletinib. Our results encourage the combination of venetoclax with entospletinib.\nThe addition of anti-CD20 monoclonal antibodies could also be beneficial.